PENGEMBANGAN TEKNIK PERMAINAN DALAM LAYANAN BIMBINGAN KELOMPOK UNTUK MENINGKATKAN PENYESUAIAN DIRI SISWA - Irawan, Edy; Rosidah, Ainur; Adiputra, Sofwan (STKIP Muhammadiyah Pringsewu, 2015)
This Study is based on the studentâs problem who is failure to achieve his happiness in life, it is caused by his adaptation incapableity. This study aimed to know the studentâs adaptation level at the first grade SMP N 2 Pringsewu in academic years 2013/2014, and formulated an effective developmental model of game technigue on group counseling service to improve studentâs adaptation in that school. This study used qualitative design. The method that used is research and development. The steps are : (1) Preliminary reseach; (2) Planning; (3) Devoloping hyphothetic model; (4) Analyzing hypothetic model; (5) Revising; (6) Limitating trial; (7) Revising tial result; (8) Extending trial; (9) Revising final model; (10) Dessiminati and socialization. The result showed that group counseling using game technique empirically proven that is efective to improve studentâs adaptation.Keywords: Group Counseling; Game Technique; Self Adjusment.